Konkurencja na rynku ziemi rolniczej - Urban, Stanisław (Competition on the Agricultural Land Market, 2006)
In Poland there has been a significant revival on the agricultural land market since the adaptation to the market economy. It was due to the privatisation of the land resources, which at that time belonged and was under the management of the Agency for Agricultural Land. In 1992-2004 that Agency sold 1479 thousand ha that is over 31% of areas that were taken over by the state. The supply of private ownership land has also increased. In addition, the demand for farmland has increased as well. It is owing to the fact that direct payments for farms were introduced. Consequently imbalance on the market of agricultural land has occurred which means that the demand is dominating over supply, and as a result prices of land increase since the competition is low. However, such a situation is varied through the whole country. Furthermore, the features that decide about land competitiveness have widened. Apart from the quality of land and its location the importance of the different features which influence the usage of such a land has been increasing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 455-460